THE STUDENTS' AND TEACHERS’ IMPRESSION TOWARD NEARPOD APPS IN LEARNING ENGLISH OF CURRICULUM MERDEKA PERSPECTIVES - HILMI, CHAERUL; HIDAYANI, SELNISTIA; PERDANA, PURNAMA RIKA (LEARNING : Jurnal Inovasi Penelitian Pendidikan dan Pembelajaran, 2024)
This article discusses using an application for Education called Nearpod. Nearpod is an application with real-time insights into student understanding through interactive lessons, gamified learning, formative assessment, and other exciting activities. Nearpod can be personalized instruction for individual students, small group assignments, or homework to differentiate and allow students to work independently, which all this feature in line with the framework of Kurikulum Merdeka. This research was done by using qualitative approach. In this article, the author wants to find students' and teacher perceptions or feedback about their experience learning and teaching English by using Nearpod in the classroom. the interview was used as the instrument in collecting main data. Hence, 5 students became the sample in this research. Besides that, the author also provides the observation as the supporting data to look on how the student engage with the apps. The data were taken from a school in Tangerang, Banten province. This school has been applying of Kurikulum merdeka for 4 years. In which, this will have a strong bond between the demand in both curriculum and this app. The result of the research shows thematic dimensions of positive and negative feedbacks. Those are memory of learning retention, creativity and critical thinking, new environment experience, advantages and disadvantages for future suggestions.